Identification of the modulators of cardiac ion channel function - Carstens, Johanna J. (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MScMedSc (Biomedical Sciences. Molecular Biology and Human Genetics))--University of Stellenbosch, 2009.